2016
DOI: 10.1039/c6ra11288a
|View full text |Cite
|
Sign up to set email alerts
|

Abuse tolerance behavior of layered oxide-based Li-ion battery during overcharge and over-discharge

Abstract: The main reason for the degradation of slightly overcharged NCM/graphite full cells was found to be the unstable crystal structure of the NCM material at a relatively high delithiation state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…The side reactions during overcharge are mainly induced by excessive high cathode potential, low anode overpotential, and elevated temperature. Under high cathode potential, the transitional metal ion at cathode such as Mn 2+ will dissolve and move from cathode to anode, eventually depositing on the anode. As the overcharge proceeds further, the oxidation of electrolyte will occur under higher cathode potential .…”
Section: Introductionmentioning
confidence: 99%
“…The side reactions during overcharge are mainly induced by excessive high cathode potential, low anode overpotential, and elevated temperature. Under high cathode potential, the transitional metal ion at cathode such as Mn 2+ will dissolve and move from cathode to anode, eventually depositing on the anode. As the overcharge proceeds further, the oxidation of electrolyte will occur under higher cathode potential .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 To date, the failure mechanisms of overcharged LIBs have been widely investigated. [11][12][13][14][15][16][17] Xu et al 11 announced that during the overcharge process, Fe (iron) dendrites continued growing upon both electrodes, which might penetrate through the separator and induce short circuiting eventually, leading to the failure of a battery. [11][12][13][14][15][16][17] Xu et al 11 announced that during the overcharge process, Fe (iron) dendrites continued growing upon both electrodes, which might penetrate through the separator and induce short circuiting eventually, leading to the failure of a battery.…”
Section: Introductionmentioning
confidence: 99%
“…Ouyang et al investigated the overcharge‐induced capacity fading mechanism through IC analysis and proposed different capacity loss mechanisms from different cathode materials . Qian et al investigated the cycle decay behavior of Li (Ni 1/3 Co 1/3 Mn 1/3 )O 2 /graphite battery during slight overcharge condition . By using IC analysis, they found that the loss of NCM materials, SEI growth, and electrolyte oxidation would happen during overcharging process.…”
Section: Introductionmentioning
confidence: 99%
“…24 Qian et al investigated the cycle decay behavior of Li (Ni 1/3 Co 1/3 Mn 1/3 )O 2 /graphite battery during slight overcharge condition. 25 By using IC analysis, they found that the loss of NCM materials, SEI growth, and electrolyte oxidation would happen during overcharging process.…”
Section: Introductionmentioning
confidence: 99%